Penerapan Dolus Eventualis Dalam Pasal 338 KUHP Menurut Perspektif Hukum Pidana Islam: Penerapan Dolus Eventualis Dalam Pasal 338 KUHP Menurut Perspektif Hukum Pidana Islam - Sholihah, Aminatus (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2019)
According to Islamic criminal law an action can be said to kill when an action is carried out by an offender who causes an act of death, the existence of a victim injured by the perpetrator to cause death, the existence of a tool used by the perpetrator to commit the act of murder, the resulting consequences from the actions committed by the perpetrator against the victim in this case the death of the victim.The intentional element contained in Dolus evantualis is applied in article 338 by looking at the state of the perpetrator when committing an act that causes death even though at first the action was carried out without the purpose and intent to kill the victim, but seen from the perpetrator's awareness and knowledge of the possible consequences will arise from these actions can already be used as an element of deliberation and can be addressed by article 338 of the Criminal Code.Whereas according to Islamic criminal law the application of Dolus eventualis in article 338 includes semi-deliberate murder and the sentence contained in article 338, namely the maximum 15-year prison sentence in accordance with the ta'zir sentence in the semi-intentional murder crime, which is ta'zir punishment this is a substitute sentence for semi-deliberate murder.